A Criterion for the Existence of Almost Periodic Solutions of Nonlinear Differential Equations with Impulsive Perturbation - Slyusarchuk, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We establish conditions for the existence of almost periodic solutions of nonlinear almost periodic differential equations with impulsive perturbation in Banach spaces without using the \( H \)-classes of these equations.